Endophytes of the tropics : diversity, ubiquity and applications - Ting, Adeline Su Yien (Boca Raton, FL, USA : CRC Press, 2020)
"Endophytes of the Tropics: Diversity, Ubiquity and Applications® is a presentation of consolidated information on endophytes from the tropical region. It provides a glimpse of the various species of endophytes in the tropics, their host plants, their applications in the various field, and some of the challenges in endophytic research. In short, this book presents an overview of and the future of endophyte research in the tropics. The book offers comprehensive coverage of the most essential topics, including: Diversity of endophytes in the tropics Beneficial application of tropical endophytes or their derivatives Highlights on some valuable endophytic species from the tropics Some commercialized products based on tropical endophytes Challenges in researching endophytes Remedial strategies to advance research on tropical endophytes This books stands apart from others as it highlights on endophytes of the tropical regions, associating the uniqueness of tropical endophytes with the rich plant diversity and ethnobotanical history. There is therefore greater possibility that novel metabolites can be isolated from the endophytes, which can be explored and harnessed for the benefit of mankind"--
OCLC-licensed vendor bibliographic record.
Keywords: Endophytes; Tropical plants -- Microbiology; SCIENCE / Life Sciences / Biology / Microbiology; SCIENCE / Life Sciences / Botany